Analysis of Sample Science Questions for Secondary School Exam in terms of Revised Bloom Taxonomy - Zerman Kepceoğlu, Gülşah; Pektaş, Murat (Kastamonu Egitim Dergisi, 2023)
Purpose: In this research, it is aimed to examine the sample questions for the exam in high school transition system published between 2018-2022 according to the revised bloom taxonomy.
Design/Methodology/Approach: The document analysis model was used and The data source of this research is the science questions in the sample questions for the central examination for secondary education institutions to admit students by examination published on the website of the General Directorate of Measurement, Evaluation and Examination by the Ministry of National Education since October 2018. Between October 2018 and December 2022, a total of 355 science questions were published and in this study all of these questions examined according to the revised bloom taxonomy.
Findings: Most of the sample questions examined are within the scope of conceptual questions. 74% of the questions published in 2018, 75% of the questions in 2019, 66% of the questions in 2020 and 2021, and 70% of the questions in 2022 are at the level of conceptual knowledge.
Highlights: Almost all of the questions are in the conceptual knowledge class and are preferred from low-level questions, and high-level questions are the last ones. Another important finding is that all of the high-level questions (58 questions) are preferred from the category “Analyze”, but not at all from the categories “Evaluate” and “Create”.
Keywords: Science Education; Fen Bilgisi Eğitimi; Revised Bloom Taxonomy; Science education; National exam; 4. Education